RANCANG BANGUN PENDEKTESIAN ASAM DAN BASA BERBASIS ARDUINO UNO - Triyono Suryo Atmojo (Jurnal Teknik, 2017)
Technological developments have left people tend to get used to working with the aid of automatic devices. The research that led to the automation has also been developed such as the detection of acid-base degree. The detector uses an Arduino Uno microcontroller components as the brains to run the program, and the pH sensor (Power of Hydrogen) as input that detect the state of a solution. In this solution and research tool used can be planned a new system. The system uses a microcontroller as a liaison between chemistry with the world of electrical technology. Produce percentage is almost close to perfect, as evidenced by the accuracy of the output of which is detected by a detector. In this study, the authors designed a detector-based acid-base arduino uno. The aim is to produce an acid-base detector with high accuracy than litmus paper sold in the market. With the alkaline acid detection devices are expected to ease the food industry, restaurants, and households in the detection of acid-base automatically. With an accuracy of ± 0.5 pH (25˚C).